Glutathione, Vitamin C, Malonodialdehyde Oxidized Low-Density Lipoprotein and Lipid Profile Levels in Type 2 Diabetic Iraqi Males - Tuleab, Shakir Faris (Al-Nahrain Journal of Science, 2018)
Diabetes is a devastating disease throughout the world. It is associated with several mechanisms, one of which is oxidative stress. Oxidative stress plays an important role in the pathogenesis and the complications of diabetes. Hyperglycemia results in overproduction of oxygen free radicals, which contributes to the progression of diabetes. This study was designed to evaluate the status of serum Glutathione, Vitamin C, Malonodialdehyde and Oxidized Low-Density Lipoprotein levels in male patients with type 2 diabetes mellitus. A total study subject of 82 were examined, including 46 patients with type 2 DM and 36 healthy individuals as a control group matched for age, sex, and body mass index (BMI). Blood samples were drawn after an overnight fasting for the determination of serum glucose, HbA1c, urea, uric acid, insulin, GSH, MAD, OX-LDL, Vit C, and lipid profile. It was found that total diabetic patients had higher FSG, HbA1c, urea, FSI, OX-LDL, MDA, TC, TG, LDL, and VLDL levels and lower UA, GSH and Vit C levels when comparing with control groups. The prevalence oxidative stress among type 2 DM patients is very high with deslipidemia is being most common continuous monitoring of glucose and lipid profile in diabetic patients is essential to reduce the mortality rate.